Competitive immunochromatographic test strips for the rapid semi-quantitative analysis of the biologically active bitter glycoside, amarogentin. Issue 1 (2nd January 2021) - Nuntawong, Poomraphie; Lohseethong, Kotchaporn; Juengwatanatrakul, Thaweesak; Yusakul, Gorawit; Putalun, Waraporn; Tanaka, Hiroyuki; Sakamoto, Seiichi; Morimoto, Satoshi
ABSTRACT: Amarogentin (AG), a biologically active secoiridoid glycoside, is responsible for the efficacy of Gentianaceae based medications. Thus, qualitative and quantitative analyses of AG are of significance for batch to batch quality control purposes. By conjugating colloidal gold nanoparticles with the AG-specific monoclonal antibody, MAb 1E9, we were able to develop a single-step competitive immunochromatographic assay (ICA) for simple quantification of the AG content in plant samples. With a limit of detection of 250 ng/mL, the analytical results were obtained after immersing the ICA test strip in the detection mixture for 15 min. This new ICA is superior to conventional ICAs as it is considerably faster due to the speed with which the test strips can be produced and the omission of the time-consuming preparation phase that was previously required to make the fiber pad. Moreover, our ICA only needs a small amount of analyte (20 µL).The reliability of the reported test strip was confirmed by comparing its semi-quantitative results with those obtained via an indirect competitive enzyme-linked immunosorbent assay (icELISA). The positive correlation between these methods (R 2  = 0.984) indicated that this new ICA could be applied for the semi-quantitative analysis of the AG content in plant samples.